Beam steering effects on remote optical measurements of pollutant emissions in heated plumes and flares. (October 2020) - Conrad, B.M.; Thornock, J.N.; Johnson, M.R.
Highlights: Remote optical measurements have potential to be sensitive to beam steering effects Three dimensionless corrections describe beam steering effects on radiative transfer Atmospheric plumes of flares are examined as an extreme case of beam steering Beam steering corrections are negligible for measurements through simulated plumes Abstract: Remote optical measurement techniques are valuable tools for the quantification of combustion-generated, climate-forcing emissions. Leveraging radiometric observations along a detector's line-of-sight, these techniques resolve column density information from which pollutant loading and emission rates can be deduced for an in situ atmospheric plume of a targeted source. One commonly neglected source of uncertainty in such measurements is beam steering – the deflection of light as it traverses the plume due to composition- and temperature-driven gradients in the real refractive index field of the plume. In this work, three correction parameters were derived from the radiative transfer equation to enable consideration of beam steering effects on these measurement techniques. A Monte Carlo procedure was performed to derive realistic optical axes through plumes of large-eddy-simulated gas flares, considered to be an extreme case of beam steering due to elevated temperature and composition gradients near the flame. Deflections of light due to beam steering were quantified at wavelengths in the visible spectrum and within three diagnostic-relevant infrared absorption bands for methane and carbon dioxide. A conservative, empirical model for the degree of beam steering was derived. Moreover, from these data, correction parameters required to account for the impact of beam steering on perceived incident intensity, optical depth, and source intensity were found to be negligible at all studied wavelengths relative to typical instrument noise. Thus, this work demonstrates that even for the extreme case of a turbulent heated flare plume, beam steering has negligible impact on the ability to quantify pollutant loading and emissions.